Standardization of soil-less nursery mixture for black pepper (Piper nigrum L.) multiplication using plug-trays - K Kandiannan, M Anandaraj, D Prasath, K B Vinitha, V Srinivasan, (Journal of Spices and Aromatic Crops, 2014)
Availability of quality planting material of high yielding varieties is a major production constraint in all black pepper (Piper nigrum L.) growing countries, and hence there is a need for technology that boosts production of quality planting material. An investigation was carried out to study the effect of different combinations of soil-less coir pith based nursery mixtures on rooting and growth of black pepper cuttings in the nursery. Among the different nursery media combinations, coir pith with Trichoderma and vermicompost recorded significantly higher growth parameters. The study confirmed that composted coir pith with vermicompost and Trichoderma is an ideal potting medium for black pepper nursery. In the second experiment, among the single node cuttings with three different maturities (collected from the serpentine method runners), maximum nursery grwoth, was recorded in the terminal portion of the runners (11-15th nodes). Similarly, higher growth parameters were recorded in the cuttings planted with full leaf compared to halfleaf cuttings. The study indicated that the rooted cuttings with full leaf from middle and top portions recorded higher growth parameters. Use of Trichoderma and vermicompost enriched coir pith in black pepper nurseries minimizes chemical fungicides besides Trichoderma that colonizes the root system of seedlings will help in preventing the infection by pathogens in the main field. Since there is no high additional cost involved, the use of Trichoderma enriched coir pith can also be adopted by commercial nurseries.